Uncovered interest parity at distant horizons: evidence on emerging economies & nonlinearities - Arnaud Mehl; Lorenzo Cappiello (European Central Bank (ECB), 2007)
This paper tests for uncovered interest parity (UIP) at distant horizons for the US and its main trading partners, including both mature and emerging market economies, also exploring the existence of nonlinearities. At long and medium horizons, it finds support in favour of the standard, linear, specification of UIP for dollar rates vis-à-vis major floating currencies, but not vis-à-vis emerging market currencies. Moreover, the paper finds evidence that, not only yield differentials widen, but that US bond yields do react in anticipation of exchange rate movements, notably when these take place vis-à-vis major floating currencies. Last, the paper detects signs of nonlinearities in UIP at the mediumterm horizon for dollar rates vis-à-vis some of the major floating currencies, albeit surrounded by some uncertainty.
Keywords: E43; F31; F41; 330; distant horizon; emerging economies; Nonlinearities; Uncovered interest parity; Zinsparität; Rendite; Anleihe; Schwellenländer; USA